Impact Of Female Parliamentarians On The Legislative Process: A Case Study Of The National Assembly Of Pakistan (2013-2023)" - Rifat Rafeeq , Dr. Abdul Basit Khan (Migration Letters, 2024)
This research paper focuses on the role of women parliamentarians for legislation in the National Assembly of Pakistan for the period 2013 to 2023. This study adopted a qualitative research method to gather primary data from the female legislators through interviews in order to establish their efforts, impacts and coping mechanisms within a masculinised political system. It was identified that women parliamentarians played an active role in legislation and specifically, the advancement of policy change in the area of women’s rights, health, and education. They were also very instrumental in the awareness creation of social justice issues, culminating to gendered provisions in general legal frameworks. However, female parliamentarians encountered many problems, such as gender discrimination, low representation in critical decision-making processes, and inadequate organizational assistance. They also had to deal with the resistance of male colleagues and societal expectations that limited their political activity. In addressing these challenges, female legislators adopted various approaches including developing good working relations, the media, constant capacity enhancement, and evidence-based lobbying for legislation. Based on the study’s findings, the following policy recommendations should be implemented to increase female parliamentarians’ legislative output: These are; creation of systematic and structured mentorship; recurrent capacity development forums; policy measures meant to promote women’s representation in the decision-making structures; and, political and administrative support to research and advocacy activities undertaken by female legislators. Moreover, the promotion of the information about the work of female parliamentarians and their problems in the society can create a more favourable environment for the female participation in politics. In this way, the successors of local policymakers and political parties should establish efficient legislative measures and targeted support of the population affected by such barriers. Thus, this research contributes to the understanding of the process of female political participation and policy advocacy in a developing country and pushes for progressive change in Pakistan..